Pendekatan Transdisipliner di Perguruan Tinggi untuk Pengembangan Industri Mainan Modern : A Study of Art, Design and Psychology on the Phenomenon of Toys as Universal Entertainment Agents - Noorsasetya, Ananta Hari (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
Product design is a further enhancement of visual art oriented towards function and mass production. In the context of toys, this phenomenon supports additional functions of toys as entertainment medium for adults for emotional release and nostalgia ,not merely as stimulation for child development. Based on product design theory, emotional theory and childhood memory as the foundation, this research explored the role of toys as universal entertainment agents to facilitate relaxation and community building. By implementing a transdisciplinary approach, higher education as the provider of the workforce has the potential to make significant contributions in the development of the modern toys industry. This writing analyzes how toys repeated design and specific art style link industry and hobby. The author would also explore how some disciplines are able to integrate to enrich the design and production of modern toys.